The Development of Students’ Discovery Learning Worksheet Based on Android in Buffer Solution - Nina Kadaritna; Fredy Pratama; M. Mahfudz Fauzi Syamsuri (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
The Development of Students’ Discovery Learning Worksheet Based on Android in Buffer Solution. The objectives of this research were to develop and determine the feasibility of Android-based learning media and to describe its characteristics, teachers’ and students’ responses to the student worksheets discovery learning based on Android in buffer solution. This research used Borg and Gall research design and development which only focused on the first five stage. The data were analyzed using descriptive statistics analysis. The expert validation showed that the average percentage on content suitability aspect, construction and readability were 89,44%, 92,85% and 92,94% and considered as very high criteria consecutively. The teachers’ responses on suitability, construction and readability aspects were 92,59%, 93,96% and 94,51% and considered as very high criteria respectively. Therefore,students’ responses on readability and attractiveness were 96,03% and 98,05% and considered as very high criteria. Based on these results, the student worksheets based on Android generated by this research is valid and worthy as sources of learning.Keywords: learning media, discovery learning model, student worksheets, android, buffer solution.